Housing production and land ownership in Albania in the context of transition. Social aspects of the transformations in the city of Gjirokastër - Βαταβάλη Φερενίκη (The Greek Review of Social Research, 2017)
The collapse of state socialism in 1989 and the transition of Albania to the free-market economy is the starting point of wide changes on land ownership and housing production, in the context of global processes. The aim of this article is to explore the processes of the transition of land ownership from a centrally planned economy to free-market economy after 1989 and until 2007, by focusing on housing production in the city of Gjirokastër. The main argument of the article is that, despite serious social inequalities, the dynamics related with land ownership and housing distribute the profits from land rent to wide social groups.